The Competencies of School Administrators Influencing School Administration in the 21st Century under Pattani Provincial Office of Learning Encouragement - จะปะกิยา มักตา; อับดุลลอฮหะซัน ฟาริด; ยี่สุ่นทรง อะห์มัด; หีมพินิจ มุซักกีด (Al-HIKMAH Journal, 2024)
This research was a survey aims to 1) study the competency level of school administrators, 2) investigate the level of school administration in the 21st century, 3) examine the relationship between the competencies of school administrators and school administration in the 21st century, and 4) scrutinize school administrators’ competencies influencing school administration in the 21st century under Pattani Provincial Office of Learning Encouragement. The sample of this study comprised 217 teachers and educational personnel affiliated with the Pattani Provincial Office of Learning Encouragement during the academic year 2023, selected through stratified random sampling the research instrument employed in this study was a questionnaire, competency level of school administrators demonstrating a reliability coefficient of .955. And school administration in the 21st century a reliability coefficient of .948 the statistical tools used for data analysis were statistical, (e.g., means, standard deviation), Pearson’s product-moment correlation coefficient, and Multiple Regression Analysis, conducted using. The research findings revealed that:1 The competencies of school administrators in the schools, both overall and in each aspect, was at a high level ,2) The school administration in the 21st century, both overall and in each aspect, was at a high level 3) The relationship between the competencies of school administrators and the school administration in the 21st century, overall, shows a significantly high positive correlation) at the statistical level of .01 4) The School administrators’ competencies in eight aspects the 21st century collectively predict school administration in the 21st century, accounting for 75.7% by Achievement motivation Analytical thinking Caring &developing others and Visioning influencing school administration in the 21st century with a statistically significant correlation at the .05 level. The equation could be summarized in raw scores as follows. = 0.783 + 0.121* + 0.147* + 0.097* + 0.215*